Factors implementing six sigma program: a case study of Sime Darby Industrial Academy / Farhana Zul Kaflee - Zul Kaflee, Farhana (Faculty of Business and Management, 2011)
Six Sigma program in many organizations simply means a program and a measure of quality that strives for near perfection. The purpose of the study is to identify the factors in implementing Six Sigma program in Sime Darby Industrial Academy. The respondents are the staffs working at Human Resources Development department which consist 30 respondents. The first objective is to examine the factors implementing Six Sigma program in Sime Darby Industrial Academy. The second objective is to examine the most dominant factors affecting the Six Sigma program in Sime Darby Industrial Academy. Follow by the third objective which is to give the recommendations in implementing Six Sigma program in Sime Darby Industrial Academy. The research methodology for this study, the researcher used Descriptive Research. The population involved in this study is the employees working at Sime Darby Industrial Academy. In this study, the researcher will use probability sampling methods which the simple random sampling (SRS) techniques in order to obtain data from the element in the population has equal chance of being selected. The researcher will use primary data and secondary data to gather the information by distributing questionnaire to the respondents. Data obtain will be compute by using Statistical Package for the Social Science (SPSS) for Windows. The techniques will be uses are the Reliability Test and the Regression Linear. The finding for this research is to identify the most dominant factors in implementing Six Sigma program which is the cultural changes is the major factors affecting in implementing Six Sigma program in Sime Darby Industrial Academy.